Association Between Circulating Proprotein Convertase Subtilisin/Kexin Type 9 Concentrations and Cardiovascular Events in Cardiovascular Disease: A Systemic Review and Meta-Analysis - Jiahui Liu (Frontiers Media S.A., 2021)
Background: A large amount of evidence suggests that proprotein convertase subtilisin/Kexin type 9 (PCSK9) inhibitors have clinical benefits in patients with cardiovascular disease (CVD). However, whether PCSK9 concentrations predict future cardiovascular (CV) events remains unclear.Methods: We conducted a meta-analysis to investigate the ability of PCSK9 concentrations to predict future CV events in patients with established CVD. A comprehensive search of electronic databases was conducted in June 2021. We included relative risk (RR) estimates with 95% CI or events of interest.Results: Eleven cohort studies including 8,471 patients with CVD were enrolled. The pooled RR of CV events for the increase in the circulating baseline PCSK9 concentrations by 1 SD showed a positive association in a random-effect model (RR 1.226, 95% CI: 1.055–1.423, P = 0.008). Similarly, the risk of the total CV events increased by 52% in the patients in the highest tertile compared with those in the lowest tertile of circulating PCSK9 concentrations (RR 1.523, 95% CI: 1.098–2.112, P = 0.012). The association between PCSK9 and CV events was stronger in stable patients with CVD, patients treated with statins, and Asian patients.Conclusions: High PCSK9 concentrations are significantly related to the increased risk of future CV events. These results enrich the knowledge of PCSK9 function and suggest the further possible clinical role of PCSK9 inhibitors.